IDENTIFIKASI STRUKTUR RESISTIVITAS DAERAH GEOTHERMAL “T” BERDASARKAN HASIL PEMODELAN 2D DATAMAGNETOTELURIK - Nur Rachmaningtias; Agus Setyawan; Imam Baru Raharjo (Youngster Physics Journal, 2014)
Resistivity structure identification of magnetotelluric data was made at geothermal area“T”, located in southern Indonesia. This process is based on the modeling result of 2-dimention magnetotelluric data. The modeling result of magnetotelluric data shows relativity structure dissemination on a scale of 0-10 ohm.m in a thickness of 1 km (clay cap), on a scale of 10-100 ohm.m in a depth of 1-2 km (reservoir zone), and on a scale of 100-1000 ohm.m in a depth of 2-3 km (heat source zone). The result of relativity structure dissemination can be used to delineate an area with geothermal prospect around 12 km2. Keywords: magnetotelluric, 2 dimension modeling, structure resistivity